Regulating Tradeoffs to Improve Rice Production - Takatsuji, Hiroshi (Frontiers in Plant Science, 2017)
Plants are sessile organisms that are continuously exposed to a wide range of environmental stresses. To cope with various stresses using limited resources, plants have evolved diverse mechanisms of “tradeoff” that enable the allocation of resources to address the most life-threatening stress. During our studies on induced disease resistance in rice, we have found some important phenomena relevant to tradeoffs between biotic and abiotic stress responses, and between stress response and plant growth. We characterized these tradeoff phenomena from viewpoints of signaling crosstalks associated with transcriptional regulation. Here, I describe following topics: 1) PTP1-dependent increased disease susceptibility of rice under low temperature and high salinity conditions, 2) OsNPR1-dependent tradeoff between pathogen defense and photosynthesis, 3) tradeoff between pathogen defense and abiotic stress tolerance in WRKY45-overexpressing rice plants, and 4) WRKY62-dependent tradeoff between pathogen defense and hypoxia tolerance. Lastly, I discuss my view regarding the significance of such tradeoffs in agricultural production that should be considered in crop breeding; that is, the tradeoffs, although they benefit plants in nature, can be rather disadvantageous in agricultural production.